Driving factors of a vegetation shift from Scots pine to pubescent oak in dry Alpine forests. (1st November 2012) - Rigling, Andreas; Bigler, Christof; Eilmann, Britta; Feldmeyer‐Christe, Elisabeth; Gimmi, Urs; Ginzler, Christian; Graf, Ulrich; Mayer, Philipp; Vacchiano, Giorgio; Weber, Pascale; Wohlgemuth, Thomas; Zweifel, Roman; et al.
Abstract: An increasing number of studies have reported on forest declines and vegetation shifts triggered by drought. In the Swiss Rhone valley (Valais), one of the driest inner‐Alpine regions, the species composition in low elevation forests is changing: The sub‐boreal Scots pine ( Pinus sylvestris L.) dominating the dry forests is showing high mortality rates. Concurrently the sub‐Mediterranean pubescent oak ( Quercus pubescens Willd.) has locally increased in abundance. However, it remains unclear whether this local change in species composition is part of a larger‐scale vegetation shift. To study variability in mortality and regeneration in these dry forests we analysed data from the Swiss national forest inventory (NFI) on a regular grid between 1983 and 2003, and combined it with annual mortality data from a monitoring site. Pine mortality was found to be highest at low elevation (below 1000 m a.s.l.). Annual variation in pine mortality was correlated with a drought index computed for the summer months prior to observed tree death. A generalized linear mixed‐effects model indicated for the NFI data increased pine mortality on dryer sites with high stand competition, particularly for small‐diameter trees. Pine regeneration was low in comparison to its occurrence in the overstorey, whereas oak regeneration was comparably abundant. Although both species regenerated well at dry sites, pine regeneration was favoured at cooler sites at higher altitude and oak regeneration was more frequent at warmer sites, indicating a higher adaptation potential of oaks under future warming. Our results thus suggest that an extended shift in species composition is actually occurring in the pine forests in the Valais. The main driving factors are found to be climatic variability, particularly drought, and variability in stand structure and topography. Thus, pine forests at low elevations are developing into oak forests with unknown consequences for these ecosystems and their goods and services.